2022
DOI: 10.3390/heritage5040176
|View full text |Cite
|
Sign up to set email alerts
|

The Victoria and Albert Museum Plaster Casts by the Nineteenth-Century Workshops of the Notre-Dame Cathedral: Scientific Analysis and Conservation

Abstract: Four nineteenth-century casts of the decoration on the north side of the exterior of the apse of the Notre-Dame Cathedral in Paris are held in the plaster casts collection at the Victoria and Albert Museum in London. The casts were manufactured by two different nineteenth-century workshops, one run by Jean Pouzadoux and the other by Auguste Malzieux. After an assessment of the condition of the casts, a scientific analysis allowed the characterization of the manufacturing materials and subsequent conservation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…The reconstructed gypsum plaster plates were based on the materials characterized on 12 V&A plaster casts produced in the nineteenth century by the Küsthardt, Notre-Dame and Franchi workshops [20]. Multianalytical studies [21] characterised the materials and revealed the simple stratigraphy of the selected casts, made of gypsum plaster and coatings [20][21][22][23][24]. In line with historical treatises [25] organic coatings such as shellac resin, linseed oil, beeswax and inorganic coatings such barites were identi ed in the original casts [21].…”
Section: Samplesmentioning
confidence: 99%
“…The reconstructed gypsum plaster plates were based on the materials characterized on 12 V&A plaster casts produced in the nineteenth century by the Küsthardt, Notre-Dame and Franchi workshops [20]. Multianalytical studies [21] characterised the materials and revealed the simple stratigraphy of the selected casts, made of gypsum plaster and coatings [20][21][22][23][24]. In line with historical treatises [25] organic coatings such as shellac resin, linseed oil, beeswax and inorganic coatings such barites were identi ed in the original casts [21].…”
Section: Samplesmentioning
confidence: 99%